Biology and Political Behavior : the Brain, Genes and Politics - The Cutting Edge. - Somit, Albert (Research in Biopolitics, 9., 2011)
This volume examines cutting edge research in the study of biology and politics and investigates the linkage between evolution, genetics, and politics, and the relationship of brain science to our understanding of politics. Several chapters provide a special focus on the use of twin studies to understand the genetics of political behaviour.